Analisis Kesulitan Belajar Terhadap Siswa Slow Learners pada Pembelajaran IPAS Kelas IV SDN 6 Porehu Sulawesi Tenggara - Albiana, Albiana; Munawir, Ahmad; Bungawati, Bungawati (Indo-MathEdu Intellectuals Journal, 2026)
This study examines the learning difficulties experienced by slow learners in Natural and Social Sciences (IPAS) in Grade IV at SDN 6 Porehu, Southeast Sulawesi. The study aims to describe the forms of learning difficulties experienced by slow learners and the factors that influence them. A qualitative approach was used, with a case study research design. The research subjects included fourth-grade teachers, IPAS teachers, and slow learners in the fourth grade. Data collection techniques were conducted through observation, in-depth interviews, and documentation studies. Data analysis was conducted using an interactive analysis model that included data reduction, data presentation, and conclusion drawing, and data validity was tested through source and technique triangulation techniques. The results showed that slow learners experienced learning difficulties in cognitive, affective, and psychomotor aspects. In the cognitive aspect, students had difficulty understanding abstract concepts, reading, and writing down their observations. In the affective aspect, students tend to be passive, lack confidence, and are hesitant in participating in learning. Meanwhile, in the psychomotor aspect, students experience difficulties in using learning tools and easily lose concentration. Internal factors that influence learning difficulties include intellectual ability and learning motivation, while external factors include learning methods, media use, and parental support.